2014
DOI: 10.1016/j.livsci.2014.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age and growth rate at onset of boar exposure on oestrus manifestation and first farrowing performance of Landrace×large white gilts

Abstract: a b s t r a c tThe objective of this study was to evaluate the effects of age and growth rate until the onset of boar exposure on oestrus manifestation and reproductive performance in Landrace  large white crossbred gilts (DanBred). Gilts were retrospectively classified into groups according to age at boar exposure -BE (140-155 and 156-170 days) and in three classes of growth rate (GR) at BE (low GR: 500-575 g/d; intermediate GR: 580-625 g/d; and high GR: 630-790 g/d). Overall, gilts had an average weight of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…An overall picture of these correlations shows that great part of the dispersion of values is due to inter‐herd variance. Variance between individuals from the same breed, reflect farm management, diet composition and ultimately the animal body growth (Magnabosco et al., 2014). Therefore, additional samples from different farms would have benefited the study, and hence the prediction model.…”
Section: Discussionmentioning
confidence: 99%
“…An overall picture of these correlations shows that great part of the dispersion of values is due to inter‐herd variance. Variance between individuals from the same breed, reflect farm management, diet composition and ultimately the animal body growth (Magnabosco et al., 2014). Therefore, additional samples from different farms would have benefited the study, and hence the prediction model.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to identify early puberty, and to produce a synchronous pubertal response to external stimuli, are both dependent on the age at the start of puberty stimulation and heat detection. When boar exposure commences earlier (140 to 160 d of age), a normal distribution in age at detected first estrus is observed in the majority of the population [56,62,63]. When gilts continue to be stimulated and monitored for longer periods (up to 260 days of age), most will eventually have a recorded estrus, however, the later maturing gilts were reported to be part of a different distribution [63].…”
Section: Effective Selection Of the Most Fertile Gilts For Entry Tmentioning
confidence: 99%
“…Beltranena et al [71] suggested that at growth rates below 0.55 kg/d the onset of puberty may be delayed. More recently, the negative relationship between age and lifetime growth rate at puberty has been confirmed [50,62,72]. Given the growth rates achieved in contemporary dam-line genotypes, few gilts are at risk of low growth rates (>0.55 kg/d), however, puberty onset will still be delayed in slower growing gilts [63].…”
Section: Effective Selection Of the Most Fertile Gilts For Entry Tmentioning
confidence: 99%
“…The stimulation should be started around 140 days of age because age at puberty has been shown to be associated with age at onset of boar exposure. 110 On the other hand, van Wettere et al 42 suggested that first boar exposure should be delayed until 182 days of age because greater synchrony occurred within gilt groups. After stimulation, gilts achieved first estrus sooner and consequently their lifetime productivity was greater.…”
Section: Construction Of Reproductive Organs and Uterine Capacitymentioning
confidence: 99%